The State of Sustainable Markets 2021 - International Trade Centre (United Nations, 2022)
This report provides new insights into the evolution of certified agriculture and forestry. It provides data about 14 major sustainability standards for bananas, cocoa, coffee, cotton, oil palm, soybeans, sugarcane, tea and forestry products. The 2021 report adds data from 2019, showing that sustainability standards continue to expand their land coverage. This report helps shape decisions of policymakers, producers and businesses, working to address systemic labour and environmental challenges through certified sustainable production.